Efficacy and Safety of a Single Dose versus a Multiple Dose Regimen of Mebendazole against Hookworm Infections in Children: A Randomised, Double-blind TrialResearch in context - Marta S. Palmeirim; Shaali M. Ame; Said M. Ali; Jan Hattendorf; Jennifer Keiser (EClinicalMedicine, 2018)
Background: Single-dose mebendazole is widely used in preventive chemotherapy against the soil-transmitted helminths (STHs) Ascaris lumbricoides, hookworm and Trichuris trichiura, yet it shows limited efficacy against hookworm and T. trichiura infections. The use of adapted treatment regimens might provide a strategy to control and eliminate STH infections in STH-persistent settings. We evaluated the safety and efficacy of the multiple dose mebendazole regimen (3 days 100 mg bid) versus a single dose of 500 mg mebendazole in a setting with high STH prevalence and high drug pressure. Methods: This randomised, double-blind clinical trial took place in a primary school on Pemba Island, Tanzania, in school-aged children (6–12 years). Using a computer random number generator (block size 10), hookworm-positive children were randomly assigned (1:1) to either a single or multiple dose regimen of mebendazole by an independent statistician. Two stool samples were collected at baseline and follow-up (18 to 22 days after treatment) for Kato-Katz analysis. The primary outcome was cure rate (CR) against hookworm. Secondary outcomes were egg reduction rate (ERR) against hookworm, CRs and ERRs against A. lumbricoides and T. trichiura, and tolerability assessed 3, 24 and 48 h post-treatment. Participants, investigators, caregivers, outcome assessors and the trial statistician were blinded. This trial is registered with ClinicalTrials.gov, number NCT03245398. Findings: 93 children were assigned to each treatment arm. 185 children completed treatment and provided follow-up stool samples. CR against hookworm was significantly higher in the multiple dose (98%) than in the single dose arm (13%, OR 389.1, 95% CI 95.2 to 2885.7%, p < 0.001). 34 and 42 children reported mild adverse events in the single and multiple dose arms, respectively. The most common events were abdominal pain, headache and diarrhoea. Interpretation: The poor performance of single dose mebendazole against hookworm infections was confirmed, but the multiple dose treatment regimen of mebendazole showed high efficacy. Hence, multiple dose mebendazole might provide a treatment strategy in given epidemiological situations to boost control and elimination of STH infections. Funding: PATH.